STRATEGI GURU DALAM MEMBANGUN MINAT MENGHAFAL AL-QUR’AN SISWA DI SMP IT AL-MUNADI MEDAN - Hasballah Thaib, Zamakhsyari Bin; Ramlah, Siti (Universitas Dharmawangsa, 2021)
This research aims: 1) to find out the teacher's strategy in building interest in memorizing the Qur'an of students at It Junior High School Al-Munadi Medan; 2) to find out the obstacles and challenges faced by teachers in building the interest of students memorizing the Qur'an at Al-Munadi Medan IT Junior High School. This research method uses qualitative. The results showed that students' interest in memorizing the Qur'an has been very good by reaching 80% of students interested in memorizing the Qur'an. Because in realizing students who memorize the Qur'an and produce hafidz Al-Qur'an is the vision and mission of Al-Munadi IT Junior High School. The efforts made by teachers and students in increasing the interest and ability to memorize the Qur'an is actively and diligently in following the guidance of memorization of the Qur'an held by SMP IT Al-Munadi every morning